2022
DOI: 10.1097/aln.0000000000004391
|View full text |Cite
|
Sign up to set email alerts
|

Review of Postoperative Respiratory Depression: From Recovery Room to General Care Unit

Abstract: Contemporary evidence suggests that episodes of respiratory depression during anesthesia recovery are associated with subsequent respiratory complications in general care units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…More importantly, none of the respiratory events were detected by hourly nursing observations [11]. Respiratory events may develop without warning, as assessment notes before critical respiratory events rarely document bradypnea [12]. Respiratory indications for the activation of a rapid response team (RRT) are probably a clinically much more relevant outcome.…”
Section: A Critical Discussion Of Respiratory Depression After Intrat...mentioning
confidence: 99%
“…More importantly, none of the respiratory events were detected by hourly nursing observations [11]. Respiratory events may develop without warning, as assessment notes before critical respiratory events rarely document bradypnea [12]. Respiratory indications for the activation of a rapid response team (RRT) are probably a clinically much more relevant outcome.…”
Section: A Critical Discussion Of Respiratory Depression After Intrat...mentioning
confidence: 99%
“…Nonetheless, oversedation in the PACU is a harbinger of respiratory complications (eg, naloxone administration) on general care wards. 26,27 Recognition is important that the use of sevoflurane or desflurane can decrease the risk of oversedation and respiratory depression, more so during longer exposures. This observation may be important for anesthetic management among patients who may be at increased risk for oversedation and respiratory depression, such as older adults, frail patients undergoing longer procedures, and those with severe obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the action of anesthetics on the respiratory response to CO 2 is different in disease states. After injection of midazolam and thiopental, the CO 2 response curve slope decreased more profoundly in subjects suffering from chronic obstructive pulmonary disease than in healthy volunteers [ 89 ]. On the basis of these studies, such patient populations should be more closely observed because they are more vulnerable to respiratory depression.…”
Section: Behavioral Characteristics Of Respiration Are Modulated By G...mentioning
confidence: 99%